The "Two-Flaps" Technique for Descemet Stripping Only. Issue 9 (September 2021) - Cohen, Eyal; Din, Nizar; Mimouni, Michael; Trinh, Tanya; Gouvea, Larissa; AlShaker, Sara; Chan, Clara C.; Slomovic, Allan R.
Abstract : Purpose: The success of Descemet stripping only (DSO) is optimized by performing a well-centered, accurately sized diameter of descemetorhexis with a smooth curvilinear border. To achieve this success, we describe a repeatable and relatively straightforward technique to optimize this descemetorhexis for DSO. Methods: The "two-flaps" technique uses the Gorovoy DSO forceps. The technique takes advantage of the flat and smooth surface of the forceps to create the desired 4-mm Descemet stripping with minimal stromal trauma along with a continuous curvilinear descemetorhexis, minimizing the risk of postoperative stromal scarring and extension of the rhexis beyond 4 mm. Results: This technique has been used successfully in 11 cases performed by 1 surgeon or directly supervised by him. All cases achieved the desired 4-mm circumference without any residual tags or visually significant stromal scarring, with successful clearing of the central cornea and endothelial cells repopulating the central stripped area. Conclusions: This technique described provides a consistent, reproducible, and relatively trauma-free peeling of Descemet membrane and associated endothelial cells/guttae to optimize the success of DSO. Abstract : Supplemental Digital Content is Available in the Text.